Translasi Narasi Visual untuk Komunitas Belajar Filsafat Melalui Narrative Extraction Method - Elmanisa, Astiti; Elmanisa, Astiti Ramdani; Bastari, Rendy Pandita; Resmadi, Idhar (Visualita Jurnal Online Desain Komunikasi Visual, 2026)
This study examines the process of translating verbal narratives into visual forms through the application of the Narrative Extraction Method (NEM) in the design of visual assets for an Indonesian philosophy learning community. The urgency of this research lies in the need for a systematic approach to identifying and extracting key narrative elements as a foundation for visual development, ensuring that the resulting visual representations accurately reflect the meaning and context embedded in the source narrative. NEM is employed as an initial approach to extract the essence of the narrative, keywords, and conceptual elements from the text before they are translated into visual forms. The design process is understood as a practice of intersemiotic translation, in which verbal meanings are transferred into a visual sign system through the use of metaphor, composition, and illustrative style. The findings indicate that NEM helps clarify the direction of visual design, particularly when dealing with narratives that are complex and rich in social and emotional contexts. However, the implementation process also involves iterations and adjustments influenced by the illustrator’s visual style and subjective preferences, resulting in visual outcomes that are not entirely linear with the initial extraction results. Nevertheless, NEM continues to function as a primary conceptual foundation that maintains the semantic connection between the narrative and its visual representation. This study highlights the importance of creative flexibility in applying systematic methods within narrative-based visual design practices.